Characterization of three new insect-specific flaviviruses: Their relationship to the mosquito-borne flavivirus pathogens - Guzmán, Hilda; Contreras-Gutiérrez, María Angélica; Travassos Da Rosa,, Amelia P.A.; Nunes, Márcio Roberto Texeira; Cardoso, Jedson Ferreira; Popov, Vsevolod L.; Young, Katherine I.; Savit, Chelsea; Wood, Thomas Gordon; Widen, Steven G.; Watts, Douglas M.; Hanley, Kathryn A.; et al. (American Society of Tropical Medicine and Hygiene, 2018)
Three novel insect-specific flaviviruses, isolated from mosquitoes collected in Peru, Malaysia (Sarawak), and the United States, are characterized. The new viruses, designated La Tina, Kampung Karu, and Long Pine Key, respectively, are antigenically and phylogenetically more similar to the mosquito-borne flavivirus pathogens, than to the classical insect-specific viruses like cell fusing agent and Culex flavivirus. The potential implications of this relationship and the possible uses of these and other arbovirus-related insect-specific flaviviruses are reviewed. Copyright © 2018 by The American Society of Tropical Medicine and Hygiene.